Comprensión de la deprivación afectiva a partir del paradigma fenomenológico – existencial - Jaramillo Moreno, Ricardo Arturo (2022)
Child abuse and specifically affective deprivation is a practice validated and transmitted to the interior of dif ferent social nucleus, family , school and state, this increases the need to take measures to upgrade and expand the existing paradigms to explain and understand. In this paper we propose an understanding of the emotional deprivation as a form of child  abuse that is deteriorating development in the potentiation of human beings and restriction of the spiritual dimension, providing vulnerability to the health and welfare. This term refers to the lack of a link and healthy enough to guarantee an adequate comprehensive development. The causes and consequences have been fully identified, though overlooked, the restriction of human capabilities themselves, these product of a series of internal and external situations that characterize and make each particular history of abuse, and therefore the understanding of this the event will be from a humanistic perspective existential more specifically from the gestalt therapy , logotherapy and existential analysis, to a proposal for intervention from referred paradigm.